2019
DOI: 10.33594/000000099
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA miR-375-3p and the Tumor Suppressor NDRG2 are Involved in Sporadic Amyotrophic Lateral Sclerosis

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…A very original contribution recently came from Freischmidt and colleagues [103] who identified, by proteomic and biochemical studies, the members of the fragile X protein [106], an RBP implicated in neural function and degeneration [107], and of proapoptotic targets such as p53. In concordance with this result, in the sALS wobbler mouse-a model displaying almost all clinical hallmarks of human ALS patients [108]-miRNA-375-3p downregulation resulted in inefficient p53 inhibition, increased production of reactive oxygen species, and induced apoptosis [109].…”
Section: Integrative Mirna-omics Studies In Alssupporting
confidence: 60%
See 1 more Smart Citation
“…A very original contribution recently came from Freischmidt and colleagues [103] who identified, by proteomic and biochemical studies, the members of the fragile X protein [106], an RBP implicated in neural function and degeneration [107], and of proapoptotic targets such as p53. In concordance with this result, in the sALS wobbler mouse-a model displaying almost all clinical hallmarks of human ALS patients [108]-miRNA-375-3p downregulation resulted in inefficient p53 inhibition, increased production of reactive oxygen species, and induced apoptosis [109].…”
Section: Integrative Mirna-omics Studies In Alssupporting
confidence: 60%
“…Two deep mechanistic studies based on extensive RNA sequencing were performed by De Santis et al and by Capauto et al In human MNs derived from mutant FUS-induced pluripotent stem cells (iPSCs), De Santis and collaborators showed the decreased levels of the MN protective miRNA-375, leading to the upregulation of ELAVL4[106], an RBP implicated in neural function and degeneration[107], and of proapoptotic targets such as p53. In concordance with this result, in the sALS wobbler mouse-a model displaying almost all clinical hallmarks of human ALS patients[108]-miRNA-375-3p downregulation resulted in inefficient p53 inhibition, increased production of reactive oxygen species, and induced apoptosis[109].Instead, in the FUS mutant MNs differentiated from mouse embryonic stem cells (ESCs), Capauto and colleagues demonstrated the upregulation of miR-409-3p and miR-495-3p and concomitant downregulation of Gria2, a subunit of the AMPA receptor triggering a cascade of MN-damaging excitotoxic events (Figure2Eand[110]). With the same rationale, whole transcriptomics was performed in SC ventral horns of post mortem sALS human donors, revealing the downregulation of neuronal genes and the upregulation of glial ones[111].…”
supporting
confidence: 57%
“…One of the primary objectives of this study was to determine whether disruption of scat expression in adult flies caused phenotypes like those observed in the wobbler mouse. While mutations in Vps54 have not been directly linked to human disease, the wobbler mouse has been used by many researchers as a model for the sporadic form of ALS because of striking similarities to ALS pathology ( Ikeda et al, 1998 ; Dennis and Citron, 2009 ; Nieto-Gonzalez et al, 2011 ; Moser et al, 2013 ; Dahlke et al, 2015 ; Schmitt-John, 2015 ; Klatt et al, 2019 ; Rohm et al, 2019 ; Cihankaya et al, 2021 ; De Nicola et al, 2021 ). It has previously been shown that scat mutants share spermatogenesis defects caused by Golgi dysfunction with the wobbler mouse ( Castrillon et al, 1993 ; Fari et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the downregulation of miR-375-3p, the inhibition of p53 is ineffective, resulting in overexpression of NDRG2, increasing the generation of ROS and creating a vicious circle. Therefore, increased miR-375-3p might be a protective mechanism to prevent cell apoptosis by decreasing p53 expression and maintaining the NDRG2 level [83].…”
Section: Mirna and Neuronal Survival And Apoptosis In Alsmentioning
confidence: 99%